Influence of skin-layer microstructure in ultrafast laser surface treatment. Issue 1 (2018) - Romoli, L.; Lazzini, G.; Gemini, L.; Fuso, F.
Abstract: In this work, the morphology of AISI 316L stainless steel surfaces, textured with ultrafast laser machining, was studied by scanning probe microscopy. In particular, correlations between the morphology and the polycrystalline microstructure of the material were searched. Topographic maps of the treated surfaces revealed a transition from small-sized to larger size and rather irregular features, driven by increase in laser fluence and depending on process parameters. In addition, a metrological analysis of the material grains demonstrated a shape and size similarity with laser-induced features attained for certain process parameters, suggesting that surface texture turns influenced by the microstructure of the skin-layer.